Ileocaecal Volvulus With an Intestinal Rotational Abnormality and Internal Hernia in a Paediatric Patient : A Case Report - Soini, Venla; Hilska, Matias; Sallisalmi, Marko; Juusela, Risto; Virkki, Ella; Raitio, Arimatias (Hindawi, 2025)
Background: Caecal volvulus in the paediatric population is uncommon, yet at worst this condition is a life-threatening surgical emergency. In children, caecal volvulus can be associated with a variety of predisposing factors such as chronic constipation, intestinal malrotation, or neurological disease.
Case Representation: We present a rare case of caecal volvulus, internal hernia, and an intestinal rotational abnormality in a previously healthy 8-year-old boy. The patient presented with a history of abdominal pain and vomiting for 3 days and was admitted to the hospital in a severe septic shock. After the initial stabilisation with fluids and vasopressors, an emergency laparotomy was performed. A necrotic caecum volvulus, a transmesocolic hernia, and an abnormal rotation of the small intestine were diagnosed. The necrotic bowel segment was resected in a right-sided hemicolectomy, after which a resection distal to medial colic artery was cut-off to achieve normal anatomy. The patient was discharged on the 12th postoperative day in good health and has since returned to normal active life without any health issues within the follow-up of 5 months.
Conclusions: Caecal volvulus and internal hernia can lead to a life-threatening condition requiring immediate surgical treatment. Rare causes of abdominal pain in children should be kept in mind when severe symptoms are present.